2017
DOI: 10.1002/jso.24811
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of postoperative delirium after cytoreduction surgery‐hyperthermic intraperitoneal chemotherapy

Abstract: This report shows an incidence of 28% of delirium, occurring after CRS-HIPEC and suggests a role for systemic inflammation in the development of postoperative delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Here we report that the NLR is a highly significant biomarker of delirium which strongly reflects IRS, M1, Th2, Th17, and IRS/CIRS activation and Tcell growth as well. As such, the present study extends previous research that high serum and CSF CRP and an increased NLR in peripheral blood are consistently reported as biomarkers or predictive risk factors of post-operative delirium [17] [19,[57][58][59][60]. Nevertheless, the immune profiles assayed here better predict delirium symptoms than NLR.…”
Section: Discussionsupporting
confidence: 88%
“…Here we report that the NLR is a highly significant biomarker of delirium which strongly reflects IRS, M1, Th2, Th17, and IRS/CIRS activation and Tcell growth as well. As such, the present study extends previous research that high serum and CSF CRP and an increased NLR in peripheral blood are consistently reported as biomarkers or predictive risk factors of post-operative delirium [17] [19,[57][58][59][60]. Nevertheless, the immune profiles assayed here better predict delirium symptoms than NLR.…”
Section: Discussionsupporting
confidence: 88%
“…11 literatures [ 9 , 15 , 17 , 19 , 21 27 ] reported the serum CRP level of POD patients and non-POD patients in the early stage after operation and analyzed the heterogeneity between the literatures in mg/L ( χ 2 = 191.74, P < 0.01). Using the random-effects model and meta-analysis showed that there was a significant difference in serum CRP level between POD patients and non-POD patients after operation [MD = 27.67, 95% CI (12.77, 42.58), Z = 3.64, P = 0.0003], as shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Literature Quality and Bias Evaluation. In this study, the cases included in the literatures [9,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] were representative, the potential risk of bias was small, and some literatures did not describe the dropout cases in detail [22,23], but the overall quality score of all literatures was 7-9 points, with good quality, as shown in Table 2.…”
Section: Literature Quality Evaluation and Risk Of Biasmentioning
confidence: 99%
“…We were interested to read the article “Incidence and predictors of postoperative delirium after cytoreduction surgery‐hyperthermic intraperitoneal chemotherapy” published in Journal of Surgical Oncology recently, which shows an incidence of 28% of delirium, occurring after cytoreduction surgery‐hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC) and suggests a role for systemic inflammation in the development of postoperative delirium. Although the results were interesting, some methodological issues should be noticed.…”
mentioning
confidence: 99%